New and little known species of oribatid mites of the subgenus Galumna (Galumna) (Acari, Oribatida, Galumnidae) from Vietnam - Ermilov, Sergey G. (Zootaxa, 2015)
Two new species of oribatid mites of the subgenus Galumna (Galumna) (Acari, Oribatida, Galumnidae) are described from soil and litter of forest zones of southern Vietnam. Galumna (G.) paramastigophora sp. nov. differs from known species of calcicola-group by the morphology of bothridial setae and length of interlamellar setae; also, the new species is similar morphologically to Leptogalumna (Aegyptogalumna) mastigophora, however, it differs from the latter by the presence of lamellar lines, morphology of interlamellar setae and absence of notogastral setae. Galumna (G.) pseudotriquetra sp. nov. is similar morphologically to Galumna (G.) triquetra, however, it differs from the latter by the length of lamellar setae, number of postanal porose areas and morphology of notogastral porose areas Aa. Supplementary description of Galumna (G.) aba and remarks to the original description of Galumna (G.) levisensilla are presented.